2005
DOI: 10.1051/ocl.2005.0154
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage and global change: the role of oil palm

Abstract: In the context of global change, potential estimations of carbon storage by the oil palm ecosystem in different ecologies have been calculated for the major productive countries in Africa, Asian and American continents. Comparisons were done with other types of planted ecosystems as eucalyptus and coconut as well as different types of natural forests. Carbon budget components as NPP, autotrophic and heterotrophic soil respiration, litter and fine litter contributions were discussed in regards to the very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 11 publications
0
42
3
3
Order By: Relevance
“…Several studies (Guo and Gifford, 2002;Schroth et al, 2002;Don et al, 2011;de Blécourt et al, 2013) reported that conversion of forest into agricultural systems, rubber or oil palm plantations leads to decreases in C org in the surface 30 cm of soil, but most of these studies assessed the early parts of the tree crop's life cycle. The reduced inputs of organic matter in agricultural systems or oil palm plantations can, according to some authors, lead to a soil C stock that is threefold less than under natural forest (Lamade and Bouillet 2005;Schroth et al, 2002). Our results, however, show that the zone-averaged soil C stock in the top 30 cm soil depth did not change significantly with time or age of plantation in either forest or non-forest derived plantations.…”
Section: Factorscontrasting
confidence: 73%
“…Several studies (Guo and Gifford, 2002;Schroth et al, 2002;Don et al, 2011;de Blécourt et al, 2013) reported that conversion of forest into agricultural systems, rubber or oil palm plantations leads to decreases in C org in the surface 30 cm of soil, but most of these studies assessed the early parts of the tree crop's life cycle. The reduced inputs of organic matter in agricultural systems or oil palm plantations can, according to some authors, lead to a soil C stock that is threefold less than under natural forest (Lamade and Bouillet 2005;Schroth et al, 2002). Our results, however, show that the zone-averaged soil C stock in the top 30 cm soil depth did not change significantly with time or age of plantation in either forest or non-forest derived plantations.…”
Section: Factorscontrasting
confidence: 73%
“…However, the environmental consequences of oil palm development are often disastrous and numerous NGOs keep alerting the international community about both the negative environmental impact and the social unfairness of the crop's development in Indonesia (Wakker 2000;Marti 2008). Processing mills are a source of air and water pollution, plantations are a major cause of deforestation, the role of biofuel production in carbon storage is still unclear, and the impact of large estates on water regulation is still under debate (Sargeant 2001;WWF 2002;Lamade and Bouillet 2005;Simorangkir 2007;Germer and Sauerborn 2008;Danielsen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It is fundamental Carbon stock is calculated to represent the effectiveness of oil palm as a biomass sink. Oil palms form an ecosystem that acts as a productive terrestrial sink, absorbs atmospheric carbon effectively, and produces biomass comparable to that of tropical forest, or more (Lamade and Bouillet 2005). However, the derived value of biomass alone cannot represent the entire scenario throughout the life cycle of an oil palm.…”
Section: Estimation Of Agb and Carbon Productionmentioning
confidence: 99%